DNA methylation signatures of adolescent victimization: analysis of a longitudinal monozygotic twin sample. Issue 11 (2nd November 2021) - Kandaswamy, Radhika; Hannon, Eilis; Arseneault, Louise; Mansell, Georgina; Sugden, Karen; Williams, Benjamin; Burrage, Joe; Staley, James R; Pishva, Ehsan; Dahir, Aisha; Roberts, Susanna; Danese, Andrea; et al.
ABSTRACT: Accumulating evidence suggests that individuals exposed to victimization at key developmental stages may have different epigenetic fingerprints compared to those exposed to no/minimal stressful events, however results are inconclusive. This study aimed to strengthen causal inference regarding the impact of adolescent victimization on the epigenome by controlling for genetic variation, age, gender, and shared environmental exposures. We conducted longitudinal epigenome-wide association analyses (EWAS) on DNA methylation (DNAm) profiles of 118 monozygotic (MZ) twin pairs from the Environmental Risk study with and without severe adolescent victimization generated using buccal DNA collected at ages 5, 10 and 18, and the Illumina EPIC array. Additionally, we performed cross-sectional EWAS on age-18 blood and buccal DNA from the same individuals to elucidate tissue-specific signatures of severe adolescent victimization. Our analyses identified 20 suggestive differentially methylated positions (DMPs) ( P < 5e-05), with altered DNAm trajectories between ages 10–18 associated with severe adolescent victimization ( ∆Beta range = −5.5%−5.3%). Age-18 cross-sectional analyses revealed 72 blood ( ∆Beta range = −2.2%−3.4%) and 42 buccal ( ∆Beta range = −3.6%−4.6%) suggestive severe adolescent victimization-associated DMPs, with some evidence of convergent signals between these two tissue types. Downstream regional analysis identified significant differentially methylated regions (DMRs) in LGR6 and ANK3 (Šidák P = 5 e-09 and 4.07e-06), and one upstream of CCL27 (Šidák P = 2.80e-06) in age-18 blood and buccal EWAS, respectively. Our study represents the first longitudinal MZ twin analysis of DNAm and severe adolescent victimization, providing initial evidence for altered DNA methylomic signatures in individuals exposed to adolescent victimization.